Yield performances of japonica introgression lines selected for drought tolerance in a BC breeding programme - He, Y.X.; Zheng, T.Q.; Hao, X.B.; Wang, L.F.; Gao, Y.M.; Hua, Z.T.; Zhai, H.Q.; Xu, J.L.; Xu, Z.J.; Zhu, L.H.; Li, Z.K. (Wiley, 2010)
With 5 tables Developing drought tolerant cultivars is a preferred strategy to solve water‐shortage facing rice farmers. A backcross (BC) breeding was initiated to improve drought tolerance (DT) of japonica hybrids in North China using an elite japonica restorer, C418, as recipient and five indica cultivars as donors. A two‐round‐selection for yield under severe drought together with a two‐round‐selection for yield under irrigation resulted in 113 BC2F8 introgression lines (ILs). Progeny testing allowed the identification of 46 (40.7%) superior‐C418‐ILs that had significantly improved yield potential under water stress and/or normal irrigation, demonstrating the power of BC breeding in exploiting favourable variation hidden in the indica gene pool for improving complex traits of japonica rice. Increased height and accelerated‐heading were major phenotypic changes correlated with improved‐yield under stress in these ILs, suggesting the possible involvement of gibberellin (GA) pathway and drought escaping. Considerable variations in yield components among these ILs indicate the presence of different underlying mechanisms. The C418‐ILs developed in this study provide useful materials for dissecting DT and yield, and for further target‐trait‐improvement by pyramiding.